Development and multi-level validation of a computational model to predict traumatic aortic injury. (September 2021) - Zeng, Wei; Caudillo, Adrian; Mukherjee, Sayak; Lee, Sang-Hyun; Panzer, Matthew B.
Abstract: Traumatic aortic injury (TAI) is one of the leading causes of fatalities in blunt impact. However, there is no consensus on the injury mechanism of TAI in traffic accidents, mainly due to the complexity of occurrence scenarios and limited real-world crash data relevant to TAI. In this study, a computational model of the aorta with nonlinear mechanical characteristics and accurate morphology was developed and integrated within a thorax finite element model that included all major anatomical structures. To maximize the model's capability for predicting TAI, a multi-level process was presented to validate the model comprehensively. At the component level, the in vitro aortic pressurization testing was simulated to mimic the aortic burst pressure. Then, a sled test of a truncated cadaver was modeled to evaluate aorta response under posterior acceleration. The frontal chest pendulum impact was utilized to validate the performance of the aorta within full body model under direct chest compression. A parametric study was implemented to determine an injury tolerance for the aorta under these different loading conditions. The simulated peak pressure before aortic rupture was within the range of the experimental burst pressure. For the sled test, the simulated chest deflection and cross-sectional pressure of the aorta were correlated with the experimental measurement. No aorta injury was observed in simulated results of both sled test and chest pendulum impact, which matched the experimental findings. The present model will be a useful tool for understanding the TAI mechanisms, evaluating injury tolerance, and developing prevention strategies for aortic injuries. Highlights: A computational model of the human aorta was developed and comprehensively validated to predict traumatic aortic injuries. The aorta FE model was created and integrated within a detailed thorax model containing all major anatomical structures. The isolated aortic model was validated against the in vitro intraluminal pressurization tests at the component level. The aorta response in the thorax model was validated by multiple mechanisms, including deceleration and chest compression.